Impact of Prior Infection on Severe Acute Respiratory Syndrome Coronavirus 2 Transmission in Syrian Hamsters - Zhang, Cheng; Guo, Zhendong; Li, Nan; Cui, Huan; Meng, Keyin; Liu, Lina; Zhao, Li; Zhang, Shanshan; Qin, Chengfeng; Liu, Juxiang; Gao, Yuwei; Zhang, Chunmao (Frontiers in Microbiology, 2021)
Prior infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) provides protective immunity against reinfection. However, whether prior infection blocks SARS-CoV-2 transmission is not yet clear. Here, we evaluated the impact of prior infection on SARS-CoV-2 transmission in Syrian hamsters. Our results showed that prior infection significantly reduced SARS-CoV-2 replication in Syrian hamsters, but sterilizing immunity was not achieved. Prior infection blocked the airborne transmission of SARS-CoV-2 from previously infected Syrian hamsters to uninfected and previously infected Syrian hamsters and substantially reduced the efficiency of direct contact transmission between previously infected Syrian hamsters, but had limited impact on SARS-CoV-2 transmission from previously infected Syrian hamsters to uninfected Syrian hamsters via direct contact in the early course of infection. Human reinfection and SARS-CoV-2 transmission between a previously infected population and a healthy population would be likely, and a higher vaccination coverage rate was needed to reach herd immunity than before expected. Our work will aid the implementation of appropriate public health and social measures to control COVID-19 pandemic.